2017
DOI: 10.1016/j.eurpsy.2017.02.482
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine as a peripheral biomarker in bipolar disorder: A meta-analysis

Abstract: Our meta-analysis provides evidence that Hcy levels are elevated in persons with BD during mania and euthymia. Peripheral Hcy could be considered as a potential biomarker in BD, both of trait (since it is increased in euthymia), and also of state (since its increase is more accentuated in mania). Longitudinal studies are needed to clarify the relationship between bipolar disorder and Hcy, as well as the usefulness of peripheral Hcy as both a trait and state biomarker in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 145 publications
2
19
1
2
Order By: Relevance
“…In this study, BD patients had significantly higher prevalence of HHcy and greater plasma Hcy levels, which was consistent with the majority of previous studies assessing HHcy (Ezzaher et al, 2011;Permoda-Osip et al, 2013) and detecting Hcy levels in acute bipolar depressive episode (Chiarani et al, 2013;Salagre et al, 2017) and in remission (Chiarani et al, 2013;Dittmann et al, 2007) of BD. Furthermore, we found sex differences in HHcy rates and Hcy concentrations in BD patients, which was in agreement with previous studies showing elevated Hcy levels and HHcy rates in male patients compared with both their corresponding healthy controls and female patients; however, no significant difference was noted between BD women and female controls (Levine, Sela, Osher, & Belmaker, 2005;Osher et al, 2004;Permoda-Osip et al, 2013;Permoda-Osip et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, BD patients had significantly higher prevalence of HHcy and greater plasma Hcy levels, which was consistent with the majority of previous studies assessing HHcy (Ezzaher et al, 2011;Permoda-Osip et al, 2013) and detecting Hcy levels in acute bipolar depressive episode (Chiarani et al, 2013;Salagre et al, 2017) and in remission (Chiarani et al, 2013;Dittmann et al, 2007) of BD. Furthermore, we found sex differences in HHcy rates and Hcy concentrations in BD patients, which was in agreement with previous studies showing elevated Hcy levels and HHcy rates in male patients compared with both their corresponding healthy controls and female patients; however, no significant difference was noted between BD women and female controls (Levine, Sela, Osher, & Belmaker, 2005;Osher et al, 2004;Permoda-Osip et al, 2013;Permoda-Osip et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Peripheral homocysteine (Hcy) has been considered as a potential biomarker for bipolar disorder (BD; Ghanizadeh, Singh, Berk, & Torabi‐Nami, ; Salagre et al, ). BD patients with hyperhomocysteinemia (HHcy) usually show abnormally high levels of Hcy in the blood (Chiarani et al, ; Dittmann et al, ; Osher, Bersudsky, Silver, Sela, & Belmaker, ; Osher, Sela, Levine, & Belmaker, ), which could increase the risk of cardiovascular disease (Chiarani et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The defects in cobalamin metabolism may involve a deficiency of homocysteine metabolism that lead to higher circulating homocysteine . A high plasma homocysteine has been proposed to relate to cardiovascular disease, multiple sclerosis and depression as well as psoriasis . A deficient gene function for iron transporter might be related to a reduced iron uptake.…”
Section: Discussionmentioning
confidence: 99%
“…41 A recent meta-analysis has concluded that serum homocysteine levels are elevated in patients with BD even during the euthymic state. 42 These findings suggest that homocysteine is both a trait and state biomarker for patients with BD. In the studies of elderly general population, the serum levels of homocysteine over 11 umol/L were found to be associated with the increased risk of dementia and atrophy of medial temporal lobe.…”
Section: Discussionmentioning
confidence: 90%